(untitled) (Conferencea, 2022)
Speaking skills are one of the most important skills we learn, as they allow us to communicate with others and express our thoughts and feelings. Understanding how to communicate effectively with peers sets the stage for positive self-esteem. This article deals with methods of generating and facilitating students speaking skills in EFL classes.